Pemberdayaan Ekonomi Masyarakat Pesisir Melaui Peningkatan Keterampilan Pengolahan Hasil Perikanan di Desa Labuan Lombok, Kecamatan Pringgabaya Kabupaten Lombok Timur - M. Yusuf; Syarif Husni; Muhammad Nursan; Aeko Fria Utama; Ni Made Nike Zeamita Widiyanti; Halimatus Sa’diyah (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
The general objective of implementing this community service is to increase the knowledge and skills of coastal communities, especially women fishermen about fish processing techniques, while the specific objectives are: (1) Increasing the knowledge and skills of women fishermen about technical, socio-economic and other aspects of fishery products processing business; (2) Showing the public about good, healthy, and environmentally friendly fish processing techniques and (3) Establishing relationships between universities, especially Mataram University and the community. The implementation of the activities is carried out using an adult education approach (andragogy) which is carried out through counseling and demonstrations to partner groups. The results of the activity show that: (1) This community service activity has been able to improve the knowledge and skills of partner groups, especially those related to: (a) technical, socio-economic and other aspects of fishery product processing (fish processing), (b) good, healthy, and environmentally friendly fishery product processing techniques; and (c) management capability of coastal community groups, especially women fishers processing fishery products in an effort to take advantage of existing potentials; and (2) This community service activity also encourages intensive communication as reciprocity between universities in this case the Faculty of Agriculture, UNRAM and coastal communities, especially women who are members of the fishermen's group processing fishery products (fish farmers in Labuhan Lombok Village, Lombok). Pringgabaya District, East Lombok Regency.